Effectiveness of domestic rural wastewater treatment in soil-plant system - Strzelczyk, Maria; Steinhoff-Wrześniewska, Aleksandra (Geology, Geophysics and Environment, 2020)
The characteristics of Polish rural agglomerations indicate that only 32% of these areas are villages typified by compact buildings where the use of a collective sewage system is economically justified. In other areas, it is necessary to apply solutions that allow for the sewage utilization in place of their creation and safe discharge into the environment, e.g. in the form of home systems based on biological processes, e.g. in soil-plant systems. The purpose of the work was to determine the soil-plant efficiency of wastewater treatment with the use of so-called energy plants. The experiment was conducted in 2012–2014 in lysimeters at a depth of 130 cm and 100 cm in diameter. These were submerged in the ground, filled with sand clay and equipped with installations enabling the drainage of gravity water in the form of lysimeter effluents. Two species of plants were used: Miscanthu giganteus and Sida hermaphrodita (L.) Rusby. They were irrigated with pre-treated domestic sewage (variant I – 1200 mm • year−1 and variant II – 1600 mm • year−1). For irrigation, sewage from a group of buildings inhabited by six families was used. Raw domestic sewage was discharged into the tank, consisting of four chambers, which constituted a relatively good level of pre-cleaning. For the irrigation of plants in the experiment, pre-treated sewage was used. In order to determine the effectiveness of wastewater treatment in the soil-plant environment, the concentrations of the following components were determined in the effluents: TSS, BOD5, COD, Ntot. The quantities of pollutants contained in the sewage were characterized by considerable variability, especially in relation to COD (390.6– 1583.0 mg O2 • dm−3) and Ntot (47.0–250.2 mg N • dm−3).